PERENCANAAN STRATEGI SISTEM INFORMASI RUMAH SAKIT DENGAN METODA WARD AND PEPPARD-CASSIDY - Imelda Retna Weningsih (Jurnal Kesehatan, 2021)
The development of information technology is increasing rapidly, causing pressure and pressure on businesses to constantly improve the quality of service by using the least possible resources. Various responses to both proactive and reactive in an organization to deal with the pressure and insistence.Results of research on the analysis of business processes in RS CK are less effective and efficient because of a lot of duplication of activity due to the information system that there does not yet support the business processes that support quality of service becomes effective.Results Information System Strategic planning towards Electronic Health Record in the form of a portfolio of applications, which are categorized based on its contribution to the business strategy and its role in business processes RS CK. The first category of strategic applications is applications that are critical to the survival of Business Strategy RS CK’s existing 6 applications. Both operational applications is applications that use RS CK today to support business success there are twelve (12) applications. Third supporting applications, there are 7 (seven) applications that are not critical to business success RS CK but rewarding. Fourth high potential applications, there are 7 (seven) applications that may be useful for business success RS CK in the future.